Designing boron-cluster-centered zwitterionic Y-shaped clocked QCA molecules. (12th November 2022) - Liza, Nishattasnim; Lu, Yuhui; Blair, Enrique P
Abstract: Quantum-dot cellular automata (QCA) is a nanoscale, transistor-less device technology. A single molecule may provide an elementary QCA device known as a cell. Molecular redox centers function as quantum dots, and the configuration of mobile charge on the dots encodes device states useful for classical computing. Molecular QCA may support ultra-high device densities and THz-scale switching speeds at room temperature. An applied electric field may be used to clock molecular QCA, providing power gain to boost weakened signals, as well as quasi-adiabatic device operation for minimal power dissipation in QCA devices and circuits. A zwitterionic, Y-shaped, three-dot molecule may function as a field-clocked QCA cell. We focus on the design of a counterion built into the center of the cell. Ab initio computations demonstrate that choice of counterion determines the number of mobile charges for encoding the device state on the three quantum dots. We use B 5 H 5 2 − or B 4 CH 5 − as the central counterionic linker for two different Y-shaped, three-dot QCA molecules. While both molecules support the desired device states, the number of trapped charges in the counterion determines the number of mobile holes on the molecular quantum dots. This, in turn, determines whether the device state is encoded by a hole or an electron. This choice of encoding determines how the molecular QCA cell responds to a clocking field. The two counterions studied here lead to two QCA molecules with opposite responses to the clock, similar to the complementary responses of PMOS and NMOS transistors to gated voltage control.